Associations of plasma LP(a), Hcy and D-D levels with the subtype of ischemic cerebrovascular disease. Issue 11 (March 2019) - Tang, Yong; Geng, Deqin
Abstract : Abstract: The relevance of LP(a), Hcy, and D-D in ischemic cerebrovascular disease remains undefined. This study aimed to assess the associations of plasma LP(a), Hcy and D-D levels with the subtype of ischemic cerebrovascular disease. Patients with ischemic cerebrovascular disease admitted to the Taixing People's Hospital were retrospectively enrolled from November 2017 to July 2018. Immunoturbidimetry was used to assess 119 LAA, 107 SAO, and 112 TIA patients for plasma LP(a), Hcy, and D-D levels. Plasma LP(a), Hcy, and D-D levels in the large artery atherosclerosis (LAA) group were significantly lower than those of the transient ischemic attack (TIA) group (all P < .05). LP(a), Hcy, and D-D levels were significantly reduced in the SAO group compared with the TIA group (both P < .05). The LAA and SAO groups showed comparable values for all the above parameters ( P > .05). LP(a), Hcy, and D-D levels differ according to the subtype of ischemic cerebrovascular disease.